2018
DOI: 10.1007/s10344-018-1198-6
|View full text |Cite
|
Sign up to set email alerts
|

A tooth wear scoring scheme for age estimation of the Eurasian lynx (Lynx lynx) under field conditions

Abstract: Within the framework of conservation actions for the Eurasian lynx (Lynx lynx), ageing of individuals is required to assess suitability for translocation and to investigate population dynamics and disease epidemiology. We aimed to develop a standardised ageing tool for free-ranging Eurasian lynx, which would be non-invasive, time-and cost-effective, and applicable under field conditions. We used tooth pictures of 140 free-ranging lynx of known age from Switzerland. Tooth colour, calculus, number of incisor tee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 46 publications
(67 reference statements)
0
33
0
Order By: Relevance
“…Animals originated from the Swiss Alps (n = 101), from the Jura Mountains (n = 65) and from a recently reintroduced population nucleus in northeastern Switzerland (n = 14). Age was determined using the following methods (Marti and Ryser-Degiorgis 2018): age of lynx clearly recognised as juveniles (small body size and milk dentation) was calculated in months based on the known narrow birth period in May-early June (Schmidt 1998, Henriksen et al 2005, Breitenmoser-Würsten et al 2007 given that they were found either alive or as fresh carcasses; age determination for all other individuals was performed by counting tooth cementum annuli in canines or incisors (Matson's Laboratory, Manhattan, MT, USA), unless the exact age was known thanks to marking procedures of lynx at the kitten age. Animals known to be older than 2 or 3 years (for females and males, respectively) thanks to repeated captures or detections by phototrapping were categorised as adults (without data about their exact age in years).…”
Section: Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Animals originated from the Swiss Alps (n = 101), from the Jura Mountains (n = 65) and from a recently reintroduced population nucleus in northeastern Switzerland (n = 14). Age was determined using the following methods (Marti and Ryser-Degiorgis 2018): age of lynx clearly recognised as juveniles (small body size and milk dentation) was calculated in months based on the known narrow birth period in May-early June (Schmidt 1998, Henriksen et al 2005, Breitenmoser-Würsten et al 2007 given that they were found either alive or as fresh carcasses; age determination for all other individuals was performed by counting tooth cementum annuli in canines or incisors (Matson's Laboratory, Manhattan, MT, USA), unless the exact age was known thanks to marking procedures of lynx at the kitten age. Animals known to be older than 2 or 3 years (for females and males, respectively) thanks to repeated captures or detections by phototrapping were categorised as adults (without data about their exact age in years).…”
Section: Animalsmentioning
confidence: 99%
“…Animals known to be older than 2 or 3 years (for females and males, respectively) thanks to repeated captures or detections by phototrapping were categorised as adults (without data about their exact age in years). Lynx age classes were defined as previously described (Marti and Ryser-Degiorgis 2018). Juveniles are lynx in their first year of life (i.e.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations